IMPLEMENTASI ALGORITMA YOLO DALAM MENDETEKSI JARAK PELANGGARAN SOCIAL DISTANCING DI RUANG TERBUKA: STUDI KASUS SMK JAKARTA RAYA 1 - SATRIA, SATRIA MAILIAN GUMELAR (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
The COVID-19 outbreak is considered a serious threat to public health today. The disease suddenly attacks the respiratory system, causing symptoms such as fever, fatigue, dry cough, and difficulty breathing. One of the alternative solutions proposed to stop the spread of this virus is the implementation of Social Distancing. Social Distancing is a measure to tackle the spread of the virus by reducing physical contact with others, such as avoiding crowds in public places like shopping malls, parks, schools, universities, airports, and workplaces, and maintaining a safe distance from others. COVID-19 emerged in Indonesia in early March 2020. At that time, President Joko Widodo urged the people to apply Social Distancing. Despite efforts in drug and vaccine development, it remains the current best solution to halt the virus's spread through this practice. This is because the virus is generally transmitted through close contact with an infected individual (within 6 feet) over a long period. In addition, transmission can occur when an infected person sneezes, coughs, or talks, allowing droplets released from the nose or mouth to float through the air and reach those around them. So, what system can help implement Social Distancing regulations effectively? And how is its implementation done? To address these issues, the author attempts to present research using the quantitative method, considered a scientific method because it adheres to scientific principles, including being concrete/empirical, objective, measurable, rational, and systematic.